Análisis jurisprudencial de las sentencias del Tribunal Constitucional Español Nros. 53/1985, 99/1994 y 136/1999. - Peñaranda Quintero, Héctor Ramón (Nómadas. Critical Journal of Social and Juridical Science, 2009)
The present investigation has the purpose of making an analytical view of the sentences of the Spanish Constitutional Court: NROS. 53/1985, 99/1994 and 136/1999, where aspects related among others things to the objective and subjective dimension of law, in the light of the protection of the fundamental rights.